99mTc-MIP-1404 SPECT/CT for Assessment of Whole-Body Tumor Burden and Treatment Response in Patients With Biochemical Recurrence of Prostate Cancer. (August 2020) - Schmidkonz, Christian; Götz, Theresa Ida; Atzinger, Armin; Ritt, Philipp; Prante, Olaf; Kuwert, Torsten; Bäuerle, Tobias; Goebell, Peter; Cordes, Michael
Abstract : Objective: This study aims to investigate the value of 99m Tc-MIP-1404 SPECT/CT for assessment of whole-body tumor burden and treatment response in patients with biochemical recurrence of prostate cancer who undergo androgen deprivation therapy (ADT) or external beam radiation therapy (EBRT). Methods: A total of 125 patients with biochemical recurrence of prostate cancer underwent 99m Tc-MIP-1404 SPECT/CT. All 364 prostate-specific membrane antigen (PSMA)–positive lesions in the field of view were assessed quantitatively to calculate PSMA-derived metabolic tumor parameters, including whole-body PSMA tumor volume and whole-body total lesion PSMA. These metrics were correlated with serum prostate-specific antigen (PSA) levels and Gleason scores. In a subset of 50 patients who underwent 99m Tc-MIP-1404 SPECT/CT before the initiation of ADT or EBRT, TL-PSMA and SUVmax were compared with radiographic response assessment by CT based on RECIST 1.1 and to biochemical response (BR) determined by changes in serum PSA levels. Results: Serum PSA levels correlated with SUVmax, whole-body PSMA tumor volume, and whole-body total lesion PSMA in patients with 1 and in those with more than 1 PSMA-positive lesion ( P < 0.05). The correlations were significant for both well-differentiated (Gleason score ⩽7) and poorly differentiated tumors (Gleason score ≥8) ( P < 0.05). The agreement between TL-PSMA derived from SPECT and BR in patients who underwent 99m Tc-MIP-1404 SPECT/CT before and after initiation of ADT was 80% (95% confidence interval [CI], 0.43–0.91; Cohen κ = 0.68; P < 0.05); in these patients, the agreement between TL-PSMA and CT was 60% (95% CI, 0.20–0.72; Cohen κ = 0.46; P < 0.05) and the agreement between BR and CT was 52% (0.07–0.61; Cohen κ = 0.34; P < 0.05). Comparable results were found for patients who underwent SPECT/CT before and after initiation of EBRT, with the strongest agreement between TL-PSMA and BR (80%; 95% CI, 0.38–0.93; Cohen κ = 0.66; P < 0.05) compared with the agreement between TL-PSMA and CT (60%; 95% CI, 0.13–0.69; Cohen κ = 0.69; P < 0.05) and between BR and CT (48%; 95% CI, 0–0.54; Cohen κ = 0.26; P = 0.11). Discordant findings between SPECT and CT were most likely due to limitations in the assessment of small lymph node metastases and bone involvement, which were detectable on SPECT but not on CT. Conclusions: The results of our study show that 99m Tc-MIP-1404 SPECT/CT is a promising method for the evaluation of treatment response in patients with biochemical recurrence of prostate cancer who undergo either ADT or EBRT. TL-PSMA for assessment of treatment response has the strongest correlation with serum PSA levels, superior to SUVmax -based evaluation and response assessment based on CT data and RECIST 1.1.